Seasonal variation on physico-chemical characters of Gaindahawa lake, Rupandehi, Nepal - Simkhada, Dinesh; Lekhak, HD (Botanica Orientalis: Journal of Plant Science, 2007)
Botanica Orientalis Vol.4(1) 2004. p.38-42